The Universe:The Complete Season Two Disc 5 - Cohen, Douglas J.; Thompson, Erik. (USA A&E HOME VIDEO, 2007)
The sky and outer space have fascinated man for centuries and the History Channel's series The Universe is the story of man's study of the cosmos from his earliest attempts to map and understand the heavens through modern day scientific studies, advances, and theories. A mix of historical footage, modern space imaging, and conceptual computer graphics presented in high-definition, the visual component of this production is absolutely breathtaking. Each of the 13 44-minute episodes begins with a general introduction of subjects ranging from the sun to individual planets, alien galaxies, the search for extra-terrestrial life, and scientific theories like the Big Bang. Each topic is then broken down into a series of segments that detail specific ideas, theories, or components integral to the understanding of the main topic as well as historical material, current studies and theories, and projections of potential future events and scientific advances. The 90-minute "Beyond the Big Bang" feature relates "the story of everything"--from the universe's formation following the "Big Bang" to its eventual projected demise from unchecked expansion dubbed the "Big Rip." Leading experts from universities and scientific institutions around the world do a great job of taking very complex subjects like galaxies with spiral density arms and relating them to easily graspable concepts like a city with a downtown core surrounded by suburbs and plagued by freeway traffic jams. Amazing photographs from the Hubble space telescope, infrared views from the Spitzer space telescope, and x-ray images from the Chandra X-ray Observatory augment understanding as do demonstrations of modern science's ability to simulate historical events like the formation of earth and to project future cosmic events. The Universe is a fascinating and understandable study of space that speaks to viewers ranging from the generally curious to the serious student of cosmology.
Language: English Subtitle : No Subtitle
Keywords: Documentary; History